Growth and Nutritional Status of Phenylketonuric Children and Adolescents - Mina Ahmadzadeh; Golbon Sohrab; Mohammadreza Alaei; Hassan Eini-Zinab; Behzad mohammadpour-Ahranjani; Samira Rastgoo; Zahra Namkhah (BMC Pediatrics, 2022)
Abstract Background The goal of this study was to assess the anthropometric and biochemical parameters of children and adolescents with phenylketonuria (PKU). Methods The participants in this cross-sectional study ranged in age from four to 18 years old. Biochemical markers such as vitamin B12, folic acid, iron, ferritin, calcium, 25-hydroxy vitamin D3, zinc, plasma phenylalanine (Phe) and tyrosine (Tyr) levels in blood were evaluated, as well as demographics and anthropometric measurements. A three-day dietary recall questionnaire was completed by all individuals. Results 80% (64) of the 80 patients (42 females, 52.5%) had typical PKU. Consanguineous marriages were found in 57.5% (46) of the patients’ parents. According to the height for age index, 17.5% of the study group (n = 14) were short or very short. According to age-related weight and body mass index (BMI), 37.5% (n = 30) and 43.8% (n = 35) of people are obese or overweight, respectively. Biochemical tests revealed increased vitamin B12 levels and 25-hydroxy vitamin D3 deficiency in 35% (n = 28) of the patients, insufficient folic acid in 12.5% (n = 10), and elevated phenylalanine levels in 70.3% (n = 45) of children under 12 years old, and adolescents 62.5% (n = 10). A high Phe intake (OR = 4.44, CI %95 = 1.27–15.57) is a risk factor for obesity and overweight. Conclusion Patients with PKU had a high rate of overweight and obesity. PKU patients who are overweight or obese do not differ from normal-weight patients in terms of dietary intake or laboratory findings (except for serum iron levels). One-third of patients with phenylketonuria were vitamin D deficient and had a BMI/A index of overweight/obese. It is recommended to use special medical food to help solve energy and nutrient deficiencies.